Post traumatic stress disorder and the associated factors among the survivors of road traffic accident attending in a specialized hospital in Dhaka - Haque, Shayla; Sultana, Nihar; Banu , Nelufar; Tahsin, Tania (Update Dental College Journal, 2022)
Background: Post traumatic stress disorder (PTSD) is the most common mental disorder occurring among survivors of road traffic accidents (RTA). It could result in long-term adverse consequences if left untreated, mainly leading to social and functional impairments of RTA survivors, which finally results in a poor quality of life. Objectives: To assess the prevalence of PTSD among the RTA survivors and the associated factors of it. Materials & methods: An institution-based cross-sectional study was carried out among 202 admitted RTA patients in the inpatient department of a specialized hospital in Dhaka city for one year duration. Data were collected from these patients using a semi structured interview administered questionnaire where the Diagnostic and Statistical Manual-IV DSM-IV(PCL-S) checklist used to assess PTSD. The collected data were analyzed by using SPSS software (Version 21) and p < 0.05 considered as significant. Results: A total 202 RTA patients were included in the study and the prevalence of probable PTSD among RTA survivors was 41.1% according to DSM-IV(PCL-S) checklist. The mean age of RTA survivors found 37.6 (±13.2) years, majority 57.4% belongs to 18-30 years age group. The mean PTSD score found was 44.1(±8.2), 9.2% RTA survivors had previous history of known depressive symptoms. Among the socio-demographic attributes, age and occupation were significantly associated with the PTSD; other accident related factors like time since accident and type of accident were strongly associated with the PTSD. Conclusion: This study found a high prevalence of PTSD among RTA survivors with some associated significant sociodemographic and accident-related factors. The findings suggest a need for early screening for PTSD among the survivors of RTA. Update Dent. Coll. j: 2022; 12(2): 14-18